T021 Synaptic plasticity mechanism explains the specificity of direct current stimulation. Issue 3 (March 2017) - Parra, L.
Abstract: Long term effects of transcranial electric stimulation with direct currents (tDCS) have been often attributed to synaptic plasticity. A number of human and animal studies provide support for this hypothesis. However, the exact mechanisms by which direct current stimulation affects synaptic plasticity remain unclear. Here we will present data on long term potentiation (LTP) and long term depression (LTD) of synaptic efficacy – the presumed cellular mechanism of learning. The experiments leverage classic plasticity induction protocols in hippocampal rodent brain slices (high frequency pulses, low frequency pulses, and theta burst stimulation). The main finding is that direct current stimulation in isolation does not affect synaptic efficacy. Only when stimulation is paired with one of these induction protocols do we observe effects on synaptic efficacy. The effects vanish in the presence of NMDA receptor blockers. The polarity of the effect depends on the induction mechanism and the site of plasticity, suggesting that the local polarization of the cellular membrane is the mediating factor. Based on these data we propose that tDCS in human experiments is task specific, not because of the exact placement of electrodes, but because stimulation only affects those synapses that are already undergoing plasticity. We predict that the most specific and effective tDCS interventions will be those that pair stimulation with a concurrent adaptation or learning protocol.